Method for preparing oleogel high internal phase pickering emulsion based on potato protein fiber and Arabic gum compound
By optimizing the composite treatment of potato protein fiber and gum acacia, a high internal phase pickering oil gel latex was prepared, which solved the problem of insufficient stability and functionality when using potato protein alone to prepare oil gels, and achieved higher stability and functional, suitable for the development of low-fat and environmentally friendly foods.
Patent Information
- Application Number
- CN202411704736.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, when using separate potato protein to prepare oil gels, stability and functionality need to be improved, and it is difficult to meet the needs of low-fat, environmentally friendly and physiological functions such as lipid-lowering and neuroprotection.
By optimizing the self-assembly conditions of potato protein fibers and compounding with gum acacia, an O/W type high internal phase pickering oil gel emulsion system with an oil-derived phase volume greater than 74% and a particle size less than 100 nm was prepared.
It significantly improves the stability, oil retention, uniformity, apparent viscosity and texture of oil gel products, provides better biocompatibility and release performance, and is suitable for food, medicine and cosmetic applications.
Smart Images

Figure CN119405041A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of food science and technology, and in particular to a method for preparing an oil gel high internal phase pickering emulsion based on a complex formed by potato protein fiber and gum arabic. Background Art
[0002] Fat is an important source of energy for the human body and for storing energy. It provides an ideal taste, flavor and processing characteristics for research in the food field and is an important part of the diet. Relevant research data show that excessive fat intake increases the risk of obesity, coronary heart disease and diabetes, posing a great threat to human health. In addition, given the intertwined influence of multiple factors such as health, environmental protection and sustainable development, as well as people's growing demand for diet, a new consumption trend has emerged. This trend emphasizes the production of low-fat, environmentally friendly foods that have physiological functions such as lipid-lowering and neuroprotection and are more beneficial to human health, in order to meet consumers' pursuit of a higher quality lifestyle.
[0003] As a natural and renewable plant protein resource, potato protein has a variety of balanced amino acid components. Its nutritional value and utilization value are extremely high. It has the ability to self-assemble under specific conditions. The protein self-assembly fibrillation makes it have better gel formation, foaming performance and emulsification properties, etc. It has a wide range of applications, especially in the development of oil gel products. It has potential application value. However, when used alone to prepare oil gel, its stability and functionality need to be improved. The present invention proposes that potato protein and gum arabic can be compounded through electrostatic interaction through process research. Compared with the processing and utilization of a single protein or polysaccharide, the electrostatic complex has been proven to be used in the stability of emulsions, controlled release, and nutrient delivery. It plays an important role, and can be used as a new green substrate and widely used in food industry, food and medicine and other processing industries.
[0004] Oil gel is a three-dimensional network structure formed by high molecular polymers, which binds lipophilic liquids inside to form a three-dimensional network that prevents their flow and gels the system. In recent years, high internal phase pickering oil gels are different from other common oil gel systems or surfactant-stabilized emulsions. Pickering emulsions stabilized by colloidal particles such as proteins and polysaccharides are not easy to aggregate, Ostwald ripen and demulsify due to the high desorption energy of particles at the interface, so this special emulsion system has excellent emulsion stability; at the same time, the fiberization modification of potato protein in the present invention reduces the interfacial tension of the oil gel and enhances the wettability of the oil-water interface. It has semi-solid structural characteristics, high resistance to gravity separation and high load capacity, and has good biocompatibility and release performance. It can be used as a carrier for active substances for delivery and controlled release in food, medicine, cosmetics and other projects.
[0005] In addition, high internal phase pickering emulsion oil gel has the characteristics of solid fat, good thermal stability, texture controllability and potential nutritional and health value, and can be used as a solid fat substitute for making biscuits, cakes and other foods. Summary of the invention
[0006] The present invention aims to provide a method for preparing a high internal phase pickering emulsion oil gel based on a complex formed by potato protein fiber and gum arabic; the method optimizes the self-assembly conditions of potato protein fiber and prepares an O / W type high internal phase pickering oil gel emulsion system with an oil phase volume greater than 74%, up to 90%, and a particle size less than 100 nm by compounding the potato protein fiber with gum arabic, thereby significantly improving the oil gel product with good stability, oil retention, uniformity, apparent viscosity, texture and other characteristics.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing an oil gel high internal phase pickering emulsion, the method comprising the following steps:
[0009] S1, incubating the potato protein aqueous solution under low pH conditions to obtain a potato protein fiber solution;
[0010] S2, mixing the potato protein fiber solution and the gum arabic solution and then freeze-drying to prepare a composite;
[0011] S3, preparing a complex solution, mixing it with the oil phase; shearing and dispersing it to obtain an oil gel high internal phase pickering emulsion.
[0012] As an embodiment, the concentration of the potato protein aqueous solution is 2-6%; the incubation temperature is 75-95° C., the incubation time is 12-60 hours; and the pH is 1.5-2.0.
[0013] As a preferred embodiment, the concentration of the potato protein aqueous solution is 3-5%; the incubation temperature is 90° C. and the time is 36-60 hours; and the pH is 1.5-2.0.
[0014] As an embodiment, the freeze-drying is to freeze-dry the emulsion at -30°C, vacuum degree 10 Pa, for 24-48 hours.
[0015] As an embodiment, the concentration of the gum arabic solution is 1-5%.
[0016] As an embodiment, the concentration of the potato protein fiber solution is 1-5%.
[0017] As an embodiment, the gum arabic solution is prepared by using water and gum arabic as raw materials, heating at 65-70° C. for 20-40 minutes, and stirring at room temperature for 1.5-2 hours.
[0018] As an embodiment, the volume ratio of the potato protein fiber solution to the gum arabic solution is 1:1 to 2:1.
[0019] As an embodiment, the concentration of the complex solution is 3-5%.
[0020] As an embodiment, the oil gel emulsion has an oil phase volume greater than 74% and less than 90%, forming an O / W type high internal phase pickering emulsion system with a particle size less than 100 nm.
[0021] As an embodiment, the shear dispersion is performed using a high-energy dispersion device, and shearing is performed at a rotation speed of 15,000 to 20,000 rp / min at room temperature for 1 to 3 minutes to obtain a crude emulsion; after freeze-drying, the oil gel product is obtained after shearing at a rotation speed of 8,000 to 10,000 rp / min for 20 to 35 seconds.
[0022] In some implementation examples, a 2-6% potato protein solution is prepared using water and potato protein as raw materials, and magnetic stirring is performed for 4h to 12h until fully hydrated. The solution pH is adjusted to 1.5-2.0, incubated at 75-95°C for 12-60h, and stirring is continued during this process. The solution is immediately taken out and freeze-dried for 24-48h at -30°C under a vacuum of 10pa, and potato protein fiber is obtained by freeze-drying. A 2% gum arabic solution is prepared using water and gum arabic as raw materials. After heating at 65-70°C for 30min, it is placed at room temperature and stirred for 1.5-2h. A 3-5% potato protein fiber solution is mixed with an arabic gum solution in a volume ratio of 1:1, 1:2, and 2:1, and the resulting complex solution is freeze-dried into a powder. Using water and composite particles as raw materials, a composite solution with a concentration of 3-5% is prepared, and corn oil is mixed in a ratio of 75% oil phase and 25% water phase. A high-energy dispersion device is used to shear at a speed of 15000-20000 rp / min at room temperature for 1-3 minutes to obtain a crude emulsion, and after freeze-drying, the oil gel product is obtained after shearing at a speed of 8000-10000 rp / min for 30 seconds. The above percentages all refer to mass fractions. According to a preferred embodiment of the present invention, the concentration of composite particles in S3 is 3%, and the oil gel product has good stability, uniformity, oil retention, apparent viscosity, texture and other characteristics.
[0023] The oil gel high internal phase pickering emulsion prepared by the above method also belongs to the protection scope of the present invention.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention utilizes the self-assembly ability of potato protein under specific conditions to form potato protein fibers with special structure and functionality. Potato protein, as a rich plant protein resource, has the characteristics of low cost, high yield and renewability. At present, there are relatively few studies on potato protein self-assembly. Protein fibrillation not only improves the utilization value of protein, but also retains the natural properties of protein, reduces energy consumption and waste emissions in the production process, and makes it more suitable for the preparation of high internal phase emulsions, introducing new green materials for the preparation of oil gels.
[0026] (2) The present invention mixes potato protein fiber and gum arabic in different proportions, and finds that the yield is the highest when the compounding ratio is 2:1, and the volume fraction reaches the maximum value, which can form a looser network structure, and this network structure can enhance the mechanical strength and anti-deformation ability of the oil gel. In addition, the addition of gum arabic promotes the rigidity and tightness of the interface film, effectively prevents the aggregation of oil droplets and the stratification of the emulsion, so that the oil gel maintains a more stable shape and performance during storage and use.
[0027] (3) The present invention uses potato protein fiber / gum arabic complex and corn oil as raw materials to prepare an oil gel system. The effect of different complex concentrations on the stability of the oil gel is explored through the oil retention rate, stability, texture, rheological properties, etc. of the oil gel, and finally the optimal addition concentration is 3%. At this time, the stability of the emulsion is maximized, and its distribution is more uniform and the combination is tighter.
[0028] (4) Potato protein fiber and gum arabic complex were used as raw materials to prepare oil gel. The potato fiber protein and gum arabic complex prepared on this basis was used in the development of oil gel. The obtained O / W type high internal phase pickering oil gel had an oil phase volume greater than 74%, with a maximum of nearly 90%, and a particle size less than 100 nm. It also showed better stability, uniformity, oil retention, apparent viscosity, texture and other properties. This innovative method is not only green and environmentally friendly, but also opens up a novel and sustainable way for the preparation of oil gel, further expanding the application potential of oil gel in effectively protecting fat-soluble active ingredients and delivering functional nutrients. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0030] Figure 1 The effect of different concentrations of potato protein solutions on protein fiber formation (fluorescence intensity) in Example 1 provided by the present invention;
[0031] Figure 2 The effect of different incubation temperatures on protein fiber formation (fluorescence intensity) in Example 1 provided by the present invention;
[0032] Figure 3 The effect of different incubation times on protein fiber formation (fluorescence intensity) in Example 1 provided by the present invention;
[0033] Figure 4 The influence of different volume ratios on the electrostatic composite volume fraction in Example 2 provided by the present invention;
[0034] Figure 5 The effect of different volume ratios on the electrostatic compound yield in Example 2 provided by the present invention;
[0035] Figure 6 SEM microscopic morphology images of the composites with different volume ratios in Example 2 provided by the present invention; wherein a is PP:GA=1:1 (50.0kx), b is PP:GA=2:1 (30.0kx), c is PP:GA=1:2 (50.0kx), d is PP-PNFs:GA=1:1 (30.0kx), e is PP-PNFs:GA=2:1 (50.0kx), and f is PP-PNFs:GA=1:2 (50.0kx);
[0036] Figure 7 The endogenous fluorescence spectra of the complexes of different volume ratios in Example 2 provided by the present invention; potato protein (PP); potato fibrous protein (PP-PNFs); potato protein-gum arabic complex (PP-GA); potato fibrous protein-gum arabic complex (PP-PNFs);
[0037] Figure 8 Light microscopic images of oil gel formed by composite particles of different concentrations in Example 3 provided by the present invention; wherein a-1%, b-2%, c-3%, d-4%, e-5%;
[0038] Fig. 9 The morphology and particle size distribution diagram of the oil gel formed by the composite particles of different concentrations in Example 3 provided by the present invention; wherein a is the emulsion sample; b is the emulsion particle size analysis;
[0039] Fig.10 The rheological behavior diagram of the oil gel formed by the composite particles of different concentrations in Example 3 provided by the present invention; wherein, (a) modulus analysis, (b) apparent viscosity analysis;
[0040] Fig.11 This is a composite dyeing diagram of the oil gel formed by composite particles of different concentrations in Example 3 provided by the present invention;
[0041] Fig.12 The texture diagram of the oil gel formed by the composite particles of different concentrations in Example 3 provided by the present invention; wherein a is a force-relative displacement analysis curve of the composite particle oil gel emulsion of different concentrations, and b is a hardness analysis diagram of the composite particle oil gel emulsion of different concentrations;
[0042] Fig.13 The effect of different concentrations of composite particles on the oil holding rate of oil gel in Example 3 provided by the present invention;
[0043] Fig.14 The effect of different concentrations of composite particles on the emulsion index of the formed oil gel emulsion in Example 3 provided by the present invention. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0045] The present invention provides a method for preparing an oil gel emulsion by using potato protein fiber and gum arabic to form a complex, comprising the following steps:
[0046] S1: Preparation of potato protein fiber:
[0047] Using water and potato protein as raw materials, a 2-6% potato protein solution is prepared, and magnetic stirring is performed for 4-12 hours until it is completely hydrated. The solution pH is adjusted to 1.5-2.0, and incubated at 75-95° C. for 12-60 hours. During this process, stirring is continued, and then the solution is immediately taken out and freeze-dried at -30° C. under a vacuum degree of 10 Pa for 24-48 hours to obtain potato protein fiber by freeze-drying.
[0048] S2: Compound of potato protein fiber and gum arabic:
[0049] A 1-5% (w / v) gum arabic solution was prepared with water and gum arabic as raw materials, heated at 65-70°C for 30 min, and then stirred at room temperature for 1.5-2 hours. A 1-5% (w / v) potato protein fiber solution was mixed with a gum arabic solution at a volume ratio of 1:1, 1:2, and 2:1, and the resulting complex solution was freeze-dried into powder.
[0050] S3: Preparation of oil gel:
[0051] With water and composite particles as raw materials, a composite solution with a concentration of 1-5% is prepared, and the mixture is mixed with corn oil in a ratio of 75% oil phase to 25% water phase. A high-energy dispersion device is used to shear at a speed of 15000-20000 rp / min at room temperature for 1-3 min to obtain a crude emulsion. After freeze drying (-30°C), the mixture is sheared at a speed of 8000-10000 rp / min for 30 seconds to obtain an oil gel product.
[0052] Example 1
[0053] In this example, potato protein fibers were prepared at different protein concentrations, incubation temperatures and times, and the effects on the production of protein fibers were investigated by measuring the fluorescence intensity. The results are as follows:
[0054] 1. Effect of different protein concentrations on potato protein fiber formation
[0055] like Figure 1 As shown, by measuring the fluorescence intensity of the protein fiber, it was found that when the potato protein concentration was 4%, the fluorescence index was the highest, indicating that the protein self-assembled fiber had the best effect. When the protein concentration was lower than 4%, the fluorescence intensity was weak, which may be because the protein concentration was too low and the protein fibers were too few to bind to the fluorescent solution ThT. When the protein concentration was higher than 4%, the fluorescence intensity decreased slightly, which may be because the protein was over-aggregated and shielded the ThT signal. Therefore, the present invention selects a protein concentration of 3% to 5%.
[0056] 2. Effect of different incubation temperatures on the formation of potato protein fibers
[0057] like Figure 2 As shown, by measuring the fluorescence intensity of the protein fibers, it was found that when the protein incubation temperature was 90°C, the fluorescence index was the highest, indicating that at this temperature, the protein self-assembly fiber effect was the best. When the temperature is too low, the protein fluorescence intensity is low, indicating that there are fewer protein fibers. This may be because the temperature is too low. Although the peptide fragments generated by the internal structure of the protein increase, the fiber structure is less and cannot bind to ThT. Because the formation of fiber self-assembly is a reversible process, when the temperature is too high, the composed protein peptide fragments are hydrolyzed, causing the fluorescence intensity to decrease. Therefore, the present invention selects a temperature of 90°C.
[0058] 3. Effect of different incubation times on the formation of potato protein fibers
[0059] like Figure 3As shown, by measuring the fluorescence intensity of the protein fibers, it was found that when the protein incubation time was 60h. The fluorescence intensity was the highest, and the protein self-assembled fiber generation index was the highest. However, through the data, it was found that during the process of protein fiber formation, when the incubation time was 36h, a substantial increase occurred, which was a rapid growth period. However, when the incubation continued, the fluorescence intensity increased slightly, and a plateau period appeared. Therefore, the present invention selects an incubation time of 36 to 60h.
[0060] A 4% potato protein solution was prepared with water and potato protein as raw materials, and magnetic stirring was performed for 10 hours until it was fully hydrated. The pH of the solution was adjusted to 1.5, and the solution was incubated at 90°C for 60 hours, with continuous stirring during the process. The solution was immediately taken out and cooled in an ice-water mixture for 10 minutes, and freeze-dried to obtain potato protein fiber. Water was further added to prepare a potato protein fiber solution for the following example experiments.
[0061] Example 2
[0062] In this example, 2% (w / v) potato protein fiber solution and 4% (w / v) gum arabic solution were mixed in different volume ratios (1:1, 1:2, 2:1), and the performance characteristics of the composite were investigated by measuring the volume fraction, yield, micromorphology, infrared spectrum and intrinsic fluorescence spectrum of the composite. The results are as follows:
[0063] like Figure 4 and 5 According to the volume fraction data of the complex, there is a significant difference in the volume fraction of the complex between the blank group and the experimental group, which increases with the change of the ratio of protein to polysaccharide. Among them, when the ratio of protein to polysaccharide is 2:1, the volume fraction of the complex reaches a maximum of 37.21%. This may be because the protein fiber solution reacts more completely with gum arabic, and it shows that compared with pure protein, protein self-assembled fibers are more conducive to the combination between protein and polysaccharide, forming a more loose network structure of the complex structure.
[0064] The yield data of the complex showed that the electrostatic binding yield of untreated potato protein and gum arabic was lower than that of potato protein and polysaccharide after fiber treatment. When the protein-polysaccharide composite ratio was 1:1, the yield increased from the original 7.74% to 15.11%. With the further increase of the composite ratio of protein-fiber solution, the yield of the protein-polysaccharide complex increased significantly, which may be due to the more complete reaction between protein and polysaccharide, and the yield also increased from 9.50% to 24.83%. When the protein-fiber composite ratio decreased and the polysaccharide content increased, the electrostatic composite yield increased from 6.26% to 9.30%, showing a small increase. The results show that the protein is more likely to participate in the reaction after self-assembly fiberization. This may be due to the generation of protein fibers that changed the internal structure of the protein molecules, rearranged and polymerized, and the electrostatic composite reaction with gum arabic was more complete, resulting in a further increase in the composite yield.
[0065] like Figure 6 As shown in the figure, the binding of protein and polysaccharide can be visually observed by scanning electron microscopy. The structure of the complex between protein self-assembled fibers and gum arabic is significantly different from that of the complex between potato protein and gum arabic. Untreated potato protein and polysaccharide appear aggregated and complexed, with a rough surface, an unclear network structure, and an irregular morphology; while the surface structure of the complex between potato protein fiber and gum arabic is clearer, showing a looser and more porous situation. The spatial structure of the complex presents a honeycomb structure, which may be due to the complex between protein and polysaccharide molecules after protein fiberization treatment, the introduction of polysaccharide molecules, and a more complete reaction. When the ratio of protein fiber to polysaccharide is 2:1, the microstructure of the composite particles is smooth and the pores are clear, and the network structure is also clearer. This may be due to the increase in the ratio of protein fiber, the saturation of polysaccharide, the complete reaction, and the high level of protein fiber and polysaccharide complex.
[0066] like Figure 7 As shown in the figure, the endogenous fluorescence spectrum can be used to detect the change in fluorescence intensity of protein-polysaccharide binding, and can also be used to evaluate the conformational changes around tryptophan residues. When the excitation wavelength is 400nm, in the complex of potato protein fiber and gum arabic, the fluorescence intensity of the fibrotic protein fiber and the fluorescence spectrum after binding with polysaccharide both show a decreasing trend and the peak width undergoes a red shift. With the addition of polysaccharide content, the peak intensity decreases significantly, while the shape of the peak does not change substantially, showing a typical fluorescence quenching phenomenon, indicating that there is an interaction between polysaccharide and protein. In addition, the maximum emission wavelength has a blue shift, indicating that the protein and polysaccharide have combined to form a complex. This may be because the addition of anionic polysaccharides increases the steric hindrance between protein particles, causing the conformation of the protein to change, and the internal microenvironment of tryptophan changes from polar to non-polar, which better improves the functional properties.
[0067] Example 3
[0068] In this example, a potato protein fiber / gum arabic complex with a volume ratio of 2:1 and different addition amounts (1-5%) was mixed with corn oil to prepare an oil gel emulsion. The effect of the concentration of the complex on the oil gel was investigated from the perspectives of the microscopic morphology, oil retention, rheology, texture, particle size, and creaming index of the oil gel emulsion. The results are as follows:
[0069] like Figure 8 and 9 , it was found from the light microscopy that the oil gel emulsions formed at different composite particle concentrations all contained relatively small droplets. When the composite particle concentration was low, the droplets were randomly distributed, and the gaps between the distributions were large. As the composite particle concentration continued to increase, more composite particles in the emulsion system adhered to the oil-water interface, resulting in a decrease in the interfacial tension of the oil gel emulsion system, a uniform distribution of the emulsion droplets, and a gradual reduction in the gaps between the droplets. When the composite particle concentration was too high, the adjacent droplets in the emulsion aggregated to increase the surface activity, the droplets crowded each other and deformed, and stacking occurred, and the droplets aggregated. This is because the higher the concentration of proteoglycan composite particles, the larger the interfacial area of the stable emulsion. The adsorption of composite particles during the homogenization process hindered the aggregation of oil droplets, so the protein content on the surface of the emulsion oil droplets reached saturation. It may also be caused by the excessive concentration of proteoglycan complexes causing flocculation between droplets.
[0070] From the particle size diagram of the oil gel emulsion ( Fig. 9 ) It can be obtained that when the concentration of the composite particles is 1%, the particle size of the emulsion is the largest. This is because the polymer concentration in the water phase is low and cannot completely cover the surface of all droplets. The droplets aggregate and the emulsion droplets increase, and the emulsion particle size also increases. With the increase of the composite particle concentration, the particle size distribution of the emulsion moves towards the direction of small particle size. When the composite particle concentration increases to 3%, the emulsion particle size shows a trend of gradually decreasing, and the droplet distribution is more uniform and less than 100nm, belonging to nano-level emulsion particles, which is conducive to the formation of a stable emulsion. This is because when the composite particle concentration is high, the possibility of adsorbing more complexes on the oil-water interface increases, so a dense interface film is formed, which can effectively organize the aggregation between droplets. The composite particle concentration continues to increase, and the particle size diagram shows the opposite result. This may be because with the increase of the composite particle concentration, the interface becomes saturated, the oil phase cannot completely cover all the composite particles, and the particles aggregate and the emulsion droplets increase, and the emulsion particle size also increases.
[0071] like Fig.10, modulus data are available. Within the scanning frequency range of 0.1-10 Hz, G′ and G″ of all oil gel samples do not have mutual intersection points (G′=G″), and G′ is higher than the G″ test frequency range, showing elasticity-dominated rheological properties, indicating that the three-dimensional network structure inside the emulsion is very stable and is less affected by the oscillation frequency. This is mainly because the structure constructed by the potato protein fiber and gum arabic restricts the flow of liquid oil and the sample is in a solid state. When the concentration is 3%, G′ and G″ form a cross-linked network between interface proteins or interface bulk proteoglycans induced by the higher homogenization pressure of the scanning frequency, which improves the gel viscoelasticity of the emulsion. When the concentration of composite particles increases to 4% and 5%, the storage modulus and loss modulus of the oil gel sample show a decreasing trend. At this concentration, the oil gel sample is in a saturated state, which leads to a decrease in the integrity of the internal structure of the gel oil.
[0072] Apparent viscosity analysis data show that all samples exhibit shear thinning behavior. As the concentration of composite particles increases, the initial apparent viscosity of the oil gel sample increases. This is because the high concentration of composite particles makes the network structure more solid and forms a stronger gel structure. However, as the shear rate continues to increase, the apparent viscosity of the oil gel sample decreases exponentially, indicating that when a higher shear rate is applied, the three-dimensional network structure formed is destroyed, resulting in a decrease in viscosity. The dynamic force generated by the sample during the shear process causes the crystalline structure to break, and the viscosity of the emulsion decreases as the shear rate increases, showing typical shear thinning behavior. It may also be because the distance between the emulsion droplets is close enough to form a network with each other, and the network is destroyed, resulting in a decrease in viscosity.
[0073] like Fig.11 As shown, laser confocal microscopy (CLSM) can be used to observe the microstructure of the emulsion, with the red fluorescent marker being the oil phase and the green marker being the water phase. The CLSM image shows that the bright red oil droplet area and the green water phase complex area form a clear contrast, indicating that the prepared oil gel emulsion system is a typical O / W type emulsion. With the increase of the composite particle concentration, the oil droplet size tends to become smaller and denser overall. When the composite particle concentration is 1% and 2%, the composite particle concentration is too low, and the oil droplets are prone to form large droplets and aggregate. As the composite particle concentration increases to 3%, the interface protein and the droplets reach stability, the droplets aggregate more tightly, but no deformation occurs, and the size of the single droplet changes, indicating that the smaller oil droplets merge, which can effectively prevent the aggregation of the emulsion. When the composite particle concentration is increased to 4% and 5%, the red oil droplets and the water phase proteins aggregate and the size increases. Compared with 3%, a small amount of aggregation occurs. This may be because when the composite particle adsorption reaches saturation, the excess proteoglycans aggregate on the outside of the oil droplets to form a thicker film and accumulate.
[0074] like Fig.12 As shown, the oil gel sample was stored in a refrigerator at 4°C, and the hardness of the oil gel was measured using a texture analyzer. When the concentration of composite particles was low, the hardness of the oil gel sample was also low. As the concentration of composite particles in the system increased, the hardness value of the oil gel continued to increase. (a) Figure shows the force-relative displacement curve. The oil gel structure formed by the composite particles showed a relatively weak response curve and a low hardness value, while the response curve and hardness value increased significantly with the increase in the concentration of composite particles. When the concentration was 3%, the oil gel showed obvious strain hardening behavior when compressed, with a relatively high hardness value (1.2N), showing a stronger gel network, which indicates that the oil droplets wrapped by the composite particles aggregated with the protein / polysaccharide molecules in the water phase, and the oil acted as an "active filler" to enhance the network structure of the emulsion. As the concentration of composite particles increased, more cross-linking occurred between unit volumes, which improved the hardness and mechanical properties of the emulsion oil gel. When the concentration of composite particles continued to increase, the hardness value decreased instead. This indicates that the protein / polysaccharide composite particle solution aggregated and easily formed grooves, which hindered the cross-linking of the composite particles. The formed network structure was poor and a uniform emulsion oil gel system could not be formed. This may be because the volume of the composite particles in the emulsion system reached the upper limit, resulting in more oil not being encapsulated.
[0075] like Fig.13 and 14 As shown in the figure, oil retention is often used to characterize the binding ability of oil gel emulsion system to liquid oil. The higher the oil retention of oil gel emulsion, the stronger the binding ability between composite particles and liquid oil, and the more stable the structure formed inside the system. It can be seen from the oil retention data that with the increase of the concentration of the complex, the oil retention of the oil gel increases from 24% to 88%. When the concentration of the complex is 1% and 2%, due to the small number of continuous phase protein / polysaccharide particles, a stable emulsion oil gel cannot be formed, and a certain amount of oil-water separation will occur. The formed network structure has a low capacity, resulting in the precipitation of liquid oil and presenting a semi-fluid state. When the protein concentration is added to 3%, there are enough protein particles connected to form a network structure, the gel network structure gradually becomes tight, the protection ability of oil droplets is enhanced, there is no obvious liquid oil precipitation, the oil retention rate is enhanced, and the obtained emulsion oil gel is stable. When the concentration of protein / polysaccharide complex was 4% and 5%, the oil holding rate decreased slightly. This was because with the increase in the concentration of the complex, the particles agglomerated, the ability of the formed network structure to wrap the oil decreased, and some liquid oil could not combine with the particles and existed in the form of liquid oil.
[0076] Depend on Fig.14The results of the creaming index show that with the gradual increase of the composite particle concentration, the emulsion creaming index shows a trend of continuous decrease, and the emulsion state presents a uniform and viscous gel. After 7 days of cold storage, when the composite particle concentration is 1%-2%, obvious water-oil separation-creaming phenomenon occurs. This may be because the composite particle concentration is too low, the oil phase cannot be completely wrapped, and a stable emulsion cannot be formed; when the composite particle concentration increases to 3%, the stability of the emulsion is improved. This is due to the interaction of droplets and the joint action of protein-polysaccharide composite gel, which leads to the formation of a dense network structure, and the emulsion also shows good storage stability; when the composite particle concentration continues to increase to 4%-5%, the creaming phenomenon of the emulsion is more obvious, showing partial liquid oil separation. This is because the increase in the concentration of composite particles in the water phase leads to the accumulation of coagulation and aggregation between emulsion droplets. It cannot be effectively controlled, resulting in the loss of stability of the emulsion.
[0077] In summary, a stable and uniform oil gel emulsion can be prepared by using potato protein fiber / gum arabic complex and corn oil. This oil gel emulsion can be used as a substitute for saturated fat and trans fat to improve food formulation and reduce the intake of unhealthy fat. Because it has a texture similar to solid fat, it can improve the texture and stability of food and extend the shelf life of food to a certain extent. In addition, oil gel can also be used as a controlled release and sustained release system to improve the activity and utilization rate of embedded substances, providing new ideas for the development and application of functional foods.
[0078] The present invention firstly utilizes the self-assembly ability of potato protein, takes 3-5% potato protein solution as raw material, and prepares potato protein fiber under the conditions of pH 1.5-2.0, 90°C, and incubation time of 36-60h. Secondly, the potato protein fiber solution is mixed with the gum arabic solution at a volume ratio of 2:1 to prepare potato protein fiber / gum arabic composite particles. Finally, 3% of the composite particles are dissolved in 25% of the aqueous phase, and then mixed with 75% of corn oil, and the oil gel product is prepared by two shear dispersions. The stability, uniformity, oil retention, apparent viscosity, texture and other properties of the product are well improved.
[0079] Finally, it should be noted that: the above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing an oil gel high internal phase pickering emulsion, characterized in that: The method comprises the following steps: S1, incubating the potato protein aqueous solution under low pH conditions to obtain a potato protein fiber solution; S2, mixing the potato protein fiber solution and the gum arabic solution and then freeze-drying to prepare a composite; S3, preparing a complex solution, mixing it with the oil phase; shearing and dispersing it to obtain an oil gel high internal phase pickering emulsion.
2. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The concentration of the potato protein aqueous solution is 2-6%; the incubation temperature is 75-95° C., the incubation time is 12-60 hours; and the pH is 1.5-2.
0.
3. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The concentration of the potato protein aqueous solution is 3-5%; the incubation temperature is 90° C. and the incubation time is 36-60 hours; and the pH is 1.5-2.
0.
4. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The freeze drying is to freeze dry the emulsion at -30°C under vacuum conditions of 10 Pa for 24-48 hours.
5. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The concentration of the gum arabic solution is 1-5%; the concentration of the potato protein fiber solution is 1-5%.
6. The method for preparing the oil gel high internal phase pickering emulsion according to claim 5, characterized in that: The gum arabic solution is prepared by using water and gum arabic as raw materials, heating at 65-70° C. for 20-40 minutes, and stirring at room temperature for 1.5-2 hours.
7. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The volume ratio of the potato protein fiber solution to the gum arabic solution is 1:1 to 2:
1.
8. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The concentration of the complex solution is 3-5%; the oil gel emulsion has an oil phase volume greater than 74% and less than 90%, forming an O / W type high internal phase pickering emulsion system with a particle size less than 100nm.
9. The method for preparing the oil gel high internal phase pickering emulsion according to claim 1, characterized in that: The shear dispersion is performed using a high-energy dispersion device at room temperature at a rotation speed of 15000-20000 rp / min for 1-3 min to obtain a crude emulsion; after freeze drying, the oil gel product is obtained after shearing at a rotation speed of 8000-10000 rp / min for 20-35 seconds.
10. An oil gel high internal phase pickering emulsion prepared by the method according to any one of claims 1 to 9.